Gold nanoparticle mediated graphene plasmon for broadband enhanced infrared spectroscopy. (6th June 2017) - Peng, Lilan; Zhang, Lei; Yuan, Jian; Chen, Chen; Bao, Qiaoliang; Qiu, Cheng-Wei; Peng, Zeping; Zhang, Kai
Abstract: Graphene plasmonics, with dynamic tunable resonance wavelength, has been successfully used in broadband plasmon-enhanced infrared spectroscopy. However, the requirement for external voltage loading makes the practical application sophisticated. In this work, the hybrid structure of graphene nanodot array (GNA) and gold nanoparticles (AuNPs) has been proposed as a passive platform for broadband infrared absorption enhancement. Numerical simulations show that the plasmon resonance peak of GNA becomes stiffer and broader when introducing AuNPs, and this is also proved by experimental results that the vibrational modes of polyethylene oxide molecule in a broad spectral range can be simultaneously enhanced. The metal-graphene hybrid plasmonic system has been proved to be a promising candidate for infrared sensing, which is significant for safety and healthy applications.